Pengaruh Pembelajaran Kitab Kuning terhadap Akhlak Santri Putri di Pondok Pesantren Terpadu Al-Madinah Jonggol Bogor - Kaimudin, Kaimudin; Suryani, Parti Fadhillawati (STIT Sirojul Falah Bogor, 2022)
Morals are the main goal and barometer of educational success, therefore Islamic Boarding Schools pay so much attention to and play an active role in shaping the character and noble character of students, one of the methods used by Islamic Boarding Schools in shaping morals is to teach the traditional Islamic book (kitab kuning), the goal of this research The purpose of this study was to determine the effect of learning the traditional Islamic book (kitab kuning) on the morals of female students at the Al-Madinah Integrated Islamic Boarding School Jonggol Bogor. In this study the author uses two forms of research methods, the first is library research, in this study the author tries to examine books and other scientific writings related to the material of the influence of the traditional Islamic book (kitab kuning) on morals discussed in this study, the second field research, namely the researchers directly involved to the field. In this study, it was concluded that the coefficient of the relationship between the influence of the Traditional Islamic book (kitab kuning) Learning and the morals of female students obtained a value of 0.623 and the rtable value (rt) for N = 32 at the 5% significance level was 0.361 and at the 1% significance level was 0.463. So learning the traditional Islamic book (kitab kuning) has a very strong influence on the morals of female students at the Al-Madinah Integrated Islamic Boarding School, Jonggol Bogor. Keywords: traditional Islamic book (kitab kuning), morals of female students